Customization options in consumer health information materials on type-2 diabetes mellitus—an analysis of modifiable features in different types of media - Krenn, Cornelia; Semlitsch, Thomas; Zipp, Carolin; Lengauer, Stefan; Shao, Lin; Schreck, Tobias; Bedek, Michael; Kupfer, Cordula; Albert, Dietrich; Kubicek, Bettina; Siebenhofer, Andrea; Jeitler, Klaus (Frontiers in Public Health, 2024)
Introduction The understanding of health-related information is essential for making informed decisions. However, providing health information in an understandable format for everyone is challenging due to differences in consumers’ health status, disease knowledge, skills, and preferences. Tailoring health information to individual needs can improve comprehension and increase health literacy. Objective The aim of our research was to analyze the extent to which consumers can customize consumer health information materials (CHIMs) for type-2 diabetes mellitus through various media types. Methods We conducted a comprehensive search for various CHIMs across various media types, such as websites, apps, videos, and printed or printable forms. A representative sample of CHIMs was obtained for analysis through blocked randomization across the various media types. We conducted a quantitative content analysis to determine the frequency of user-centered customization options. Cross-comparisons were made to identify trends and variations in modifiable features among the media. Results In our representative sample of 114 CHIMs, we identified a total of 24 modifiable features, which we grouped into five main categories: (i) language, (ii) text, (iii) audiovisual, (iv) presentation, and (v) medical content. Videos offered the most customization opportunities (95%), while 47% of websites and 26% of apps did not allow users to tailor health information. None of the printed or printable materials provided the option to customize the information. Overall, 65% of analyzed CHIMs did not allow users to tailor health information according to their needs. Conclusion Our results show that CHIMs for type-2 diabetes mellitus could be significantly improved by providing more customization options for users. Further research is needed to investigate the effectiveness and usability of these options to enhance the development and appropriate provision of modifiable features in health information.